Desarrollo de algoritmos para la selección de canales espectrales en redes inalámbricas de radio cognitiva usando las estrategias rectiva y proactiva - López-Sarmiento, Danilo Alfonso; Salamanca- Cespez, Jorge Enrique; Gallego-Torres, Adriana Patricia (Revista Científica, 2017)
The Cognitive Radio (CR) is the paradigm that allows optimizing the efficiency of the electric radio spectrum through a dynamic management based on sensing, decision, sharing and spectral mobility, being the decision maker responsible for selecting the best Channels for the transmission of data from cognitive nodes (SUs), depending on the requested quality of service (Best Effort (BE) or Real Time (RT)). The existing literature implicitly proposes the use of a reactive strategy for the selection of such bands; However, this implies that SU requests will only be processed once they arrive at the base station (BS) of the cognitive network, generating additional delays in sending the data. This article proposes the use of the proactive strategy proposed in (López, Rivas y Pedraza, 2017), thus pretending that the processing of spectrum assignment requests for SUs is carried out more quickly or efficiently (less processing time at the BS), thereby optimizing the spectral decision step in CR. The methodology used, part of the use of a real database that includes the presence or absence of primary or licensed users (PUs) in the GSM cellular band characterized by Bayesian Networks (López, Ordoñez y Rivas, 2016), and where the ranking of available channels in a slot Of time for allocation to SUs (sorted from best to worst channel) and SUs ranking (organized according to requested resources, giving priority to Real Time requests) is implemented through algorithms based on Topsis and FAHP. The results show that the proactive system reduces channel allocation time to SUs without degrading PU communication.